Inclusão social no programa de um computador por aluno: análise a partir do regime de informação - Lima, Janecely Silveira de (2015)
The contemporary society is constructed by the influence of means and communication processes, as well as the culture and its educational processes, with the emphasis on network computer and internet, facilitating information access. In the current scenario, the processes of social inclusion have opened space to discuss and research technological solutions. In this way, the states must develop public information policies to inclusion. However, it is required to consider that create operational mechanisms are not enough to formulate and promote a suitable policy in an information regime in favor of digital inclusion because its mechanisms such as information transference actions will be also considered its storage, its communication, its access and its use. Faced with this situation, this research aims to analyze the information regime that has been realized PROUCA in Paraíba state and its reach in the area of social inclusion. Specifically, it aims to map PROUCA information regime; to know the information artifacts used in the inclusion process offered by the program; to investigate the information actors, its application and its satisfaction benefited by PROUCA. To achieve this certain objectives, this research is structured in seven chapters which are valid to the theme categories used and its methodology discussion. According to methodology proceedings, it is classified such as field study, qualitative approach and -exploratory research. The corpus is based on five schools to verify the program satisfaction and its laptops’ use, adopted such as research techniques questionnaire application with fifteen students, an interview with schools’ managers, and also narrative method with ten teachers. It concludes that PROUCA achieved students’ digital inclusion. It was observed that is important to continue its inclusion and social processes. Finally, this research mapped and analyzed the information regime with the indicatives of information actions. In the final considerations, it puts forward various ideas to future researches to confirm that PROUCA achieved its digital inclusion and to present its information regime.